A formação de constelações: o caso da indústria global de transporte aéreo - Lazzarini, Sérgio G. (2004)
Constellations are alliances among multiple autonomous firms, such that these groups compete against each other in the same orsimilar industries for both clients and members. Airline carriers, in particular, have not only formed formal groupings in a multilateral fashion – which we call “explicit constellations” – but have also engaged in a web of bilateral ties configuring alternative groups of firms that have more bilateral ties to one another than to firms outside their group – which we call “implicit constellations”. We find that explicit constellations tend to grow by luring firms holding diverse resources and that are associated with key members through an implicit group. At the same time, members of an explicit group tend to create implicit associations with partners holding resources that are similar to their own resources, thereby creating a cluster of firms adjacent to the explicit constellation. Explicit associations also tend to exhibit more inertia over time than implicit ones, possibly due to the larger non-redeployable investments and contractual commitments required for the formation of explicit groups.